Clinical Care Pathways for Patients With Hepatitis C: Reducing Critical Barriers to Effective Treatment. (6th January 2016) - Howes, Nik; Lattimore, Sam; Irving, William Lucien; Thomson, Brian James
Abstract : New therapies with the potential to eradicate HCV are available. Engagement of infected individuals with care is the major barrier to realising this vision. We describe an enhanced care pathway leading to a sustained increase in indices of engagement. Abstract: Background. Engagement of individuals infected with hepatitis C virus (HCV) with care pathways remains a major barrier to realizing the benefits of new and more effective antiviral therapies. After an exploratory study, we have undertaken an evidence-based redesign of care pathways for HCV, including the following: (1) reflex testing of anti-HCV-positive samples for HCV RNA; (2) annotation of laboratory results to recommend referral of actively infected patients to specialist clinics; (3) educational programs for primary care physicians and nurses; and (4) the establishment of needs-driven community clinics in substance misuse services. Methods. In this study, we conducted a retrospective cohort study of progression through care pathways of individuals with a new diagnosis of HCV infection made between January 2010 and January 2012. We also analyzed patient flow through new care pathways and compared this with our baseline study of identical design. Results. A total of 28 980 samples were tested for anti-HCV antibody during the study period and yielded 273 unique patients with a new diagnosis of HCV infection. Of these, 38% were tested in general practice, 21% were tested in substance misuse services, 23% were tested in secondary care, and 18% were tested in local prisons. Overall, 80% of patients were referred to specialist clinics, 70% attended for assessment, and 38% commenced treatment, in comparison to 49%, 27%, and 10%, respectively, in the baseline study. Referral rates from all testing sources improved. Conclusions. This study provides timely evidence that progression through care pathways can be enhanced, and it demonstrates reduction of key barriers to eradication of HCV.